Perinatal palliative care education: An integrative review - Ratislavová, Kateřina; Bužgová, Radka; Vejvodová, Jana (Nurse education today, 2019)
OBJECTIVES: The aim of this review was to analyze the effectiveness of teaching healthcare professionals in perinatal palliative care, methods of evaluating the teaching, and the teaching strategies used. DESIGN: An integrative review. METHODS: A systematic search was conducted for English language peer reviewed publications of any research design via SCOPUS, Medline/PubMed, EBSCOhost, Science Direct, ERIC, Web of Science, Wiley, Nursing Ovid, and ProQuest databases. Fourteen research papers published between 2002 and 2017 that met the selection criteria were included in the review. FINDINGS: All 14 studies considered perinatal bereavement education to be effective. Eight studies reported statistical improvements in knowledge, security/comfort in providing end-of-life care, or increased perceptions of the emotional care needs of bereaved families, after attending an educational program. Questionnaires or interviews were used to evaluate the educational programs. Innovative teaching strategies, in particular, were evaluated positively (e.g., simulation, discussion, and arts-based methods). CONCLUSION: Perinatal palliative care education is essential in pregradual education for midwives and neonatal nurses. Other research is vital for finding out the effectiveness of this education for pregraduate nursing students. Perinatal palliative care education programs need to be available in postgraduate education for professionals who encounter perinatal death and bereaved families in hospital and community care.
Keywords: paliativní péče; ošetřovatelství novorozenců; studenti ošetřovatelství; Education, Nursing; studium ošetřovatelství; Humans; ztráta blízké osoby; lidé; Neonatal Nursing; Students, Nursing; Palliative Care; Bereavement